STATISTIK SPASIAL KEPADATAN PENDUDUK TERHADAP KEJADIAN MALARIA DI KABUPATEN PURWOREJO DENGAN MENGGUNAKAN GIS - Sulistyawati, . (Universitas Ahmad Dahlan, 2012)
Background: Malaria was a problem in tropical countries including Indonesia. Purworejo regency lay on Central Java Province is a low malaria endemic area but in the end of year 2010 outbreak occurred. Malaria influenced by behavior, social economic condition include the population density. Objective: To determine the relationship between malaria incidence and population density using GIS tool (spatial statistic). Methods: This type of study is analytic research with GIS as tool analysis. Sample time frame is Nov 2010-March 2011 and the unit research for population density is village. Results: Majority Village in Purworejo categorized in low population density. Malaria incidence at Nov 2010-March 2011 lay on the village with low population density. Result of Spatial statistic (using Geoda) spatially weighted regression shows that no relationship between malaria incidence and population density, z value = -0,800; p= 0,432 (p > 0, 05) Conclusion: There was no relationship between malaria incidence and population density (spatial statistic using Geoda). Key words: malaria, GIS, population density